2015
DOI: 10.1371/journal.pone.0129900
|View full text |Cite
|
Sign up to set email alerts
|

A Socio-Demographic Examination of Adults Responding to Governmental Vaccination Recommendations during the Japanese Rubella Outbreak of 2013

Abstract: BackgroundIn 2013 a rubella outbreak occurred among Japanese people of working-age which resulted in 14,357 reported cases. The Japanese government subsequently recommended voluntary vaccination or rubella antibody testing for young women (15–49 years of age) who were planning to conceive and for adult men, children, and other persons in potential contact with pregnant women at home. However, the expense and time involved for vaccination, antibody testing and visiting a clinic may represent a major barrier to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 12 publications
3
10
2
Order By: Relevance
“…The present study found that partner's current desire for pregnancy did not affect adult men's participation in the rubella catch-up program. This nding is in contrast to our previous study conducted in 2014, which found that partner's current desire for pregnancy was a major factor associated with adult men's voluntary rubella antibody testing and vaccination [14]. This difference in results is reasonable because, at the time of the rst survey, during the 2013-2014 rubella outbreak, the government recommendation for voluntary rubella vaccination targeted only women and men with a desire to conceive who could not con rm a rubella vaccination history [4].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present study found that partner's current desire for pregnancy did not affect adult men's participation in the rubella catch-up program. This nding is in contrast to our previous study conducted in 2014, which found that partner's current desire for pregnancy was a major factor associated with adult men's voluntary rubella antibody testing and vaccination [14]. This difference in results is reasonable because, at the time of the rst survey, during the 2013-2014 rubella outbreak, the government recommendation for voluntary rubella vaccination targeted only women and men with a desire to conceive who could not con rm a rubella vaccination history [4].…”
Section: Discussioncontrasting
confidence: 99%
“…Being able to con rm a rubella vaccination history was also signi cantly associated with antibody testing. These results are consistent with our previous report of the results of a 2014 survey [14]. In the present study, we also found that awareness of congenital rubella syndrome was not signi cantly associated with rubella antibody testing in the multivariate analyses.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Spatial heterogeneity in susceptibility could act as the key to discriminating the metapopulation model from homogeneous models, and our approach was unable to capture that aspect. It should be remembered that the susceptible pocket was observed mainly among males aged 35–49 years in Japan [ 19 , 20 ], which we intend to address in the forthcoming study with age structured model. The fraction of this “high risk” subpopulation may vary by prefecture and heterogeneous contact patterns would also differ.…”
Section: Discussionmentioning
confidence: 99%
“…The enlightenment activity promoting vaccinations for the unimmunized people in these generations would be vital for elimination of rubella. A research suggested that additional initiatives for persons who do not believe that they directly benefit from vaccination is needed [ 36 ]. In Japan, most full-time workers can hardly find time to get vaccinations in week days [ 7 ].…”
Section: Discussionmentioning
confidence: 99%